Ultraviolet light induces binding of antibodies to selected nuclear antigens on cultured human keratinocytes. - LeFeber, W P (1984)
Antibodies which bind to different nuclear antigens in tissue sections or in permeabilized cell cultures are useful markers of subsets of connective tissue disease, especially of lupus erythematosus (LE), but whether these antibodies are able to react with these intracellular sequestered antigens in vivo and cause immunologic tissue damage has been a matter of much debate. We report experiments which show that ultraviolet light-irradiated, cultured human keratinocytes bind IgG antibodies from the sera of LE patients with either monospecific anti-SSA/Ro, anti-RNP, or anti-Sm activity, which implies that these antigens have been made accessible on the cell surface by ultraviolet irradiation. Normal human sera or LE patient's sera with anti-double-stranded DNA, anti-single-stranded DNA, or antihistone activity do not bind to the surface of irradiated human keratinocytes. In control experiments, all antisera produced the expected patterns of nuclear and cytoplasmic staining of fixed permeabilized, unirradiated keratinocytes. Careful study of the viability and permeability of irradiated keratinocytes by several techniques showed that this apparent cell membrane expression of extractable nuclear antigens (SSA/Ro, RNP, and Sm) following irradiation was seen on injured keratinocytes whose cell membranes were intact, but not on dead cells. It is particularly significant that all six monospecific anti-SSA/Ro sera bound to irradiated keratinocytes, since this antibody antigen system is highly associated with photosensitive cutaneous LE.